Changes of the intradermal oxygen tension after modeling of myocardium necrosis in different stages of ischemic preconditioning. - Stanishevskaya, N. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Cardiovascular diseases continue to occupy a leading position in the structure of morbidity in the world. Some authors think short periods of ischemia with making the myocardium more resistant to the long coronary occlusion. This cardioprotective mechanism was named ischemic preconditioning (IPC). A lot of authors believe that short periods of hypoxia contribute to the resistance of myocardium to hypoxic injuries. Objective. The purpose was to investigate the intradermal oxygen tension on the model of the noncoronary necrosis of myocardium in different stages of the ischemic preconditioning. Methods. The study was conducted on the white Wistar rats. The intradermal oxygen tension was investigated at different stages of ischemic preconditioning. First stage was right after hypoxic training, the second stage was a day after last one. Also this index was studied at the modeling of myocardial necrosis on intact animals and myocardial necrosis following after ischemic preconditioning. Transcutaneous oximeter Radiometer TCM-2 (Denmark) was used for determine the intradermal oxygen tension. Also histological sections of the myocardium of ventricles were studied at different stages of ischemic preconditioning and noncoronarogenic necrosis. Results. It was found the intradermal oxygen tension reflects the change in tissue oxygenation, observed during hypoxic training and myocardial necrosis. A minimal intradermal oxygen tension was found at modeling necrosis in the first 2 hours after the hypoxic training. The highest mortality rate among animals was found during the same period of time. Conclusion. It was indicated the positive impact of ischemic preconditioning on the process of adaptation to myocardial necrosis, it was confirmed by the positive dynamics of intradermal oxygen tension.